Strategi pelaksanaan edukasi diet diabetes melitus sebagai penerapan prinsip etik beneficence - Permana, Daffa Mohammad; Arofiati, Fitri (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Diet is a key aspect of diabetes mellitus management, as it aims to achieve and maintain near-normal blood glucose and lipid levels, prevent acute and chronic complications, and improve the patient's quality of life. Purpose: To determine the strategies for implementing diabetes mellitus diet education as an application of the ethical principle of beneficence in nursing. Method: The research design used a literature review using Google Scholar as the e-resource data source, using the keywords